Influence of Nitrogen on Growth Performance of Hybrid and Inbred Rice (Oryza sativa L.) Varieties in Boro Season (The Agriculturists, 2010)
Field experiments were conducted during boro season of 2002 and 2003 at the Bangladesh Rice Research Institute (BRRI) farm having silty clay loam soil. Hybrid variety Sonarbangla-1 and BRRI hybrid dhan1 and modern inbred variety BRRI dhan29 were used in the experiments. Zero to 160 kg N ha-1 with 40 kg interval and different application schedules, chlorophyll meter based (SPAD35) N application and urea supper granules (USG) @ 80 kg N ha-1 were used as N treatments. During boro 2002, BRRI hybrid dhan1 had 10-15% higher tiller number, leaf area index (LAI) and crop growth rate (CGR) than Sonarbangla-1 and BRRI dhan29. Among the N managements, N9 (USG), N5 (160 kg N ha-1 with basal), N6 (160 kg N ha-1 without basal), and N7 (SPAD based N application with basal) showed 10-15% higher plant height, tiller hill-1, LAI and CGR. During boro 2003, Sonarbangla-1 and BRRI hybrid dhan1 had 10-15% higher plant height, tiller hill-1, LAI and CGR compared to the BRRI dhan29. Among the N management, N9 (USG), N5, N6, N7, N3 (120 kg N ha-1 with basal) and N4 (120 kg N ha-1 without basal) treated plots performed better in terms of growth. The LAI and CGR were reduced by 20-25 % at 60 DAT during 2003 compared to 2002 due to cold and the growth of BRRI dhan29 was restricted much.